Bootstrap Financing as a Capital Raising Strategy in Ikat Weaving Enterprises - Yulita Milla Pakereng; Melkianus Radja (Faculty of Economics and Business Udayana University, 2023)
Financial bootstrapping is a creative and non-conventional financing strategy by MSME actors to reduce dependence on external funding sources. This study aims to describe the implementation of the bootstrap financing method in obtaining a source of capital for MSMEs running the ikat weaving businesses. Using the samples of 167 ikat business owners in the district of Kambera of the regency of Sumba Timur in the province of Nusa Tenggara, this study used quantitative descriptive analysis techniques. The results show that ikat businesses use bootstrap financing strategies, including independent funding of the owners (including borrowed or invested funds from relatives), receivables management, sharing resources with other businesses, delaying payments to protect cash, and making use of subsidies. From the six indicators of bootstrap financing, the study found that the ikat businesses do not implement one strategy regarding inventory management. Keyword:bootstrap financing, MSME, and capital